Genetic screening strategy for children with hereditary spherocytosis in Jiangxi Province of China - Wu, Chongjun; Xu, Zhongjin; Wan, Qian; Chen, Feng; Ye, Yao; Wang, Hong (Frontiers in Pediatrics, 2025)
ObjectiveThis study aims to provide a comprehensive summary of the clinical phenotypic characteristics of children with anemia of unknown etiology, particularly focusing on the early detection of hereditary spherocytosis (HS) and exploring genetic screening strategies for this condition in childhood.MethodsThe study included children with anemia whose underlying cause could not be definitively identified through routine clinical diagnosis. Clinical data was collected and genetic diagnosis of HS was confirmed using next-generation sequencing. Statistical analysis was conducted to evaluate the clinical characteristics of children with HS.ResultsA total of thirty children with unexplained anemia were included in the study, resulting in a gene detection diagnostic rate of 80%. This included the identification of five non-HS-related congenital anemia genes (16.66%, 5/30) and nineteen cases of hereditary spherocytosis (HS). Upon initial diagnosis, the clinical features of HS were not significantly distinct compared to other forms of anemia.ConclusionIn Jiangxi, China, our strategy of genetic screening for these children is feasible after excluding the common causes of anemia, such as nutritional anemia, G-6-PD deficiency, thalassemia, autoimmune hemolytic anemia, and myelopoietic abnormalities in children. This is an exploration to establish a genetic screening strategy for children with HS, and more detailed genetic screening strategies need to be further studied and explored. Next-generation sequencing remains the main method for the diagnosis and differential diagnosis of HS.